1997
DOI: 10.1037/0022-006x.65.6.1047
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-month follow-up of eye movement desensitization and reprocessing (EMDR) treatment for posttraumatic stress disorder and psychological trauma.

Abstract: The present study is a 15-month follow-up of the effects of eye movement desensitization and reprocessing (EMDR) therapy on the functioning of 66 participants, 32 of whom were diagnosed with posttraumatic stress disorder (PTSD) prior to treatment, PTSD participants improved as much as those without the diagnosis, with both groups maintaining their gains at 15 months. At 15-month follow-up, the three 90-min sessions of EMDR previously administered (S.A. Wilson, L.A. Becker, & R. H. Tinker, 1995) produced an 84%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
1
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 29 publications
6
90
1
6
Order By: Relevance
“…42 Table 59 (Appendix 1) provides a selection of studies that have reported the long-term efficacy of psychological interventions for PTSD patients that have met diagnostic criteria and have been treated as part of a randomised trial (RT) or randomised controlled trial (RCT). Studies that have reported long-term follow-up data beyond 12 months but have not been incorporated in Table 59 include, for example: studies where the original sample did not meet PTSD formal diagnostic criteria, 42,44 studies where other diagnostic groups such as acute stress disorder were the primary focus of intervention; 45 studies where the focus of intervention was not primarily the alleviation of PTSD symptoms; 46 or studies where the long-term follow-up focused upon a single cohort of patients. 47 The remaining longterm follow-up studies that are here reported are diverse in nature, as illustrated in Table 59.…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…42 Table 59 (Appendix 1) provides a selection of studies that have reported the long-term efficacy of psychological interventions for PTSD patients that have met diagnostic criteria and have been treated as part of a randomised trial (RT) or randomised controlled trial (RCT). Studies that have reported long-term follow-up data beyond 12 months but have not been incorporated in Table 59 include, for example: studies where the original sample did not meet PTSD formal diagnostic criteria, 42,44 studies where other diagnostic groups such as acute stress disorder were the primary focus of intervention; 45 studies where the focus of intervention was not primarily the alleviation of PTSD symptoms; 46 or studies where the long-term follow-up focused upon a single cohort of patients. 47 The remaining longterm follow-up studies that are here reported are diverse in nature, as illustrated in Table 59.…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…These include (a) wait list controls (Rothbaum, 1997;Wilson et al, 1995Wilson et al, , 1997, (b) Veterans Administration (VA) standard care (Boudewyns & Hyer, 1996;Jensen, 1994), (c) biofeedback-assisted relaxation (Carlson, Chemtob, Rusnak, Hedlund, & Muraoka, 1998), (d) muscle relaxation (Vaughan et al, 1994), (e) active listening (Scheck et al, 1998), (f ) individual psychotherapy in an HMO environment (e.g., exposure, cognitive, psychodynamic; Marcus et al, 1997), (g) exposure therapies (Vaughan et al, 1994;Ironson et al, 2002;Rogers et al, 1999), and (h) combinations of exposure and cognitive therapies (Devilly & Spence, 1999;Lee et al, in press). This range of comparisons appears well matched to exposure therapy which has been compared to (a) wait list controls (Keane et al, 1989), (b) VA standard care (Boudewyns & Hyer, 1990;Cooper & Clum, 1989), (c) stress inoculation training and supportive counseling (Foa, Rothbaum, Riggs, & Murdock 1991;Foa et al, 1999), and (d) cognitive restructuring with or without a relaxation control (Marks et al, 1998;Tarrier et al, 1999).…”
Section: Emdr In Comparison To Cbt Treatments For Ptsdmentioning
confidence: 99%
“…The most rigorous EMDR civilian studies (e.g., Lee et al, 2002;Marcus et al, 1997;Rothbaum, 1997;Scheck et al, 1997;Wilson et al, 1995Wilson et al, , 1997 have reported substantial clinical effects, and generally indicated that 77-90% of clients no longer suffer from PTSD in 3 to 10 hours of treatment. Large effect sizes have been reported on multiple measures with no relapse at 3-15-month follow-up (Maxfield & Hyer, 2002;Van Etten & Taylor, 1998).…”
Section: Emdr In Comparison To Cbt Treatments For Ptsdmentioning
confidence: 99%
“…However, the studies in these meta-analyses had mostly small sample sizes ( N = 14–67) and covered diverse traumas varying from natural disasters to interpersonal trauma. Even though some studies examining the effectiveness of EMDR included children with subthreshold PTSD in their sample (De Roos et al, 2017; Diehle, Opmeer, Boer, Mannarino, & Lindauer, 2014; Kemp, Drummond, & McDermott, 2010; Wilson, Becker, & Tinker, 1997), no research has yet specifically focused on the effect of EMDR to reduce distress in children with medically related subthreshold PTSD, nor on predictors of EMDR treatment effect in this population. It is very important to identify and reduce subthreshold PTSD in children with medically related trauma to prevent these children developing full diagnostic PTSD and growing up with unresolved trauma and anxieties regarding medical treatment, since this may harm their medical adherence and their (mental) health later in life.…”
Section: Introductionmentioning
confidence: 99%